Systematic Literature Review: The Effect of Work Posture on Musculoskeletal Disorders in Goods Loading and Unloading Workers - Giranza, Virgian; Husna, Jihaan Hazrati; Tanjung, Sofyan Alri Ansyah; Purba, Sri Hajijah (PROMOTOR, 2024)
In lifting and transporting activities, many are still done manually, so in this activity, it is necessary to have the correct work posture when carrying out lifting and transporting goods. Lifting activities with the wrong working posture can increase the risk of occupational diseases, namely musculoskeletal disorders. This study aims to find out whether there is an influence of work posture on musculoskeletal disorders. The research method used is a literature review of seven journals that have been selected based on inclusion criteria. The results of this study showed that in lifting and transporting activities, work posture affects musculoskeletal disorders, so there is a need to improve the abnormal working posture in lifting activities.